Feeding behavior of a group of women in Family Health Strategy - Viviane Euzébia Pereira Santos; Nayara Mendes Cruz; Laísla Alves Moura; Jaqueline Gonçalves Moura; Khésia Kelly Cardoso Matos (Universidade Federal de Santa Maria, 2012)
Objective: to analyze the nutritional state and feeding behavior in adult women in units of Family Health Strategy. Since eating is one of the factors conditioning the nutritional status and, consequently, the physical and psychological health. Method: quantitative research developed from a collective case study, in which the data were collected through semi-structured interviews with open and closed questions between January and February 2008. The study population comprised 58 women and data collection was conducted through semi-structured interview, during January and February 2008. Results: from the interview found that the average age of the interviews is 42 years, 91.4% have children, 56,9% did not practice physical activities. The results show also that 51.7% of women with normal weight, with about 19 weight% and 29.3% were obese. Conclusion: proving thus that obesity increasingly becomes a major public health problem